Novel Mutations Identified in the Chinese Han Population with Keratoconus by Next-Generation Sequencing - Binbin Chen; Xiaoning Yu; Xin Zhang; Hao Yang; Yilei Cui; Xingchao Shentu (Journal of Ophthalmology)
Aim. To identify novel mutations in keratoconus (KC) susceptibility genes in the Chinese Han population. Methods. A total of fifty-two patients with primary KC were recruited. Blood samples were collected, and genomic DNA was isolated from peripheral blood leukocytes. The entire coding region, intron-exon junctions, and promoter regions of sixteen known KC susceptibility genes were screened with next-generation sequencing technology. All identified variants were further confirmed using the Sanger sequencing technology. The Sorting Intolerant from Tolerant (SIFT), MutationTaster, and PolyPhen 2 programs were used to predict the effect of amino acid substitution on protein. Results. After removing twelve known SNPs (single nucleotide polymorphisms) and three variants predicted to be harmless, nine novel mutations were identified in eight of the fifty-two patients, including c.455C > T:p.P152L in FNDC3B; c.3636_3637del:p.R1212fs in COL4A4; c.5015G > T:p.R1672L, c.3798dupA:p.P1267fs, and c.28G > A:p.A10T in MPDZ; c.1940C > T:p.P647L in DOCK9; c.127_128insGGC:p.Q43delinsRQ in POLG; c.3019G > A:p.V1007I in IPO5; and c.624 + 7− > A in TGFBI. All nine mutations in the patients with KC were heterozygote. Conclusion. This study enlarged the gene profile of KC and should be further confirmed by well-powered, genome-wide association studies (GWAS) of Han Chinese patients.